Mineralogical and geochemical characteristics of uranium-rich fluorite in El-Missikat mineralized granite, Central Eastern Desert, Egypt - Raslan, Mohamed Fahmy (Geologija, 2009)
A unique, highly radioactive variety of fluorite mineral has been recorded in the uranium occurrence of El-Missikat sheared granite pluton. In this occurrence, the uranium assumes different forms, including its presence as discrete, visible, secondary minerals, rare uraninite and its association withthe jasperoid and silica veinlets. However, in some other parts of the sheared zone, the uranium was found to be solely incorporated with fluorite crystals, filling vein let sand fractures without any other manifestation. This paper focuses on the relevant mineralogical and geochemical characteristics of this unique fluorite variety. In addition to an investigation with binocular and polarizing microscopes, the separated fluorite grains were analyzed using an environmental scanning electron microscope (ESEM) and a field-emission scanning electron microscope. In addition to this, some fluorite crystals were subjected to electron microprobeanalyses. While the fluorite accounted for as muchas 20% of the sheared granite samples studied, it was found to range from 82 to 96 % in the different size fractions of the separated heavy mineral content. In some partsof the separated fluorite crystals, uranium in quantities of up to 2200 ppm was found to be heterogeneously distributed in the fluorite lattice, regardless of its coloration.
Keywords: Egipt; Egypt; granit; mineral; minerali; puščave; radioaktivne snovi; uran